LIMITED DELEGATION AND FIRM CONTROL: A PRINCIPAL-AGENT ACCOUNT OF SOUTHERN AFRICAN DEVELOPMENT COMMUNITY (SADC) DECISION-MAKING ON ZIMBABWE’S LAND ISSUE (Journal of International Studies, 2021)
This paper accounts for Southern African Development Community (SADC) decision-making on Zimbabwe’s land issue from the year 2000 onwards. Guided by the principal-agent model, this paper argues that the delegation and control dynamics emerging from SADC’s principal-agent institutional structure and relationships shaped the regional organisation’s (RO’s) decisions on Zimbabwe’s land issue. This study adopted a qualitative methodology to explore this proposition utilising both primary and secondary sources of data. Primary data were collected through semi-structured key informant interviews and official documents such as SADC communiqués, while secondary data were gathered from published books, journal articles, newspaper articles and other related materials. Thematic analysis was the method used to analyse the data. The findings revealed that the member states (principal) limited the delegation of decision-making uthority to the SADC (agent) and the principal’s firm control of the agent were key factors shaping SADC outcomes on Zimbabwe’s land issue. These principal-agent dynamics enabled member states to control SADC’s decisions on Zimbabwe’s land issue. Conversely, there was also opportunistic agent behaviour that resulted in decisionsthat injured the principal’s interests. Such decisions included the Tribunal’s fateful ruling on Zimbabwe’s land reform programme. Overall, this paper contributes to the existing body of knowledge by re-contextualising the principal-agent model in a new setting, which is SADC decision-making on Zimbabwe’s land issue.